An empirical study of physical activity and sports affecting mental health of university students - Lu Congsheng; Lu Congsheng; Sumaira Kayani; Amna Khalid (Frontiers in Psychology, 2022)
Physical activity (PA) and sports are extremely essential elements for physical and mental health among adolescents. Around 30% of 16 years old and above in Malaysia have mental health issues. For this purpose, 512 university students from Malaysia were surveyed through social media, with 74% response rate. Structural equation model partial least square (SEM-PLS) was used to examine the effect of PA and sports on mental health. The results revealed that both PA (b = 0.402, p < 0.001) and sports (b = 0.330, p < 0.001) significantly predict mental health among university students. The model explained 35.8% variance in mental health. The study suggests that PA and sports activity need to be promoted among university students to control prevailing mental health issues in adolescents.